Bimbingan Teknik Budidaya Tumbuhan Obat Untuk Penyediaan Simplisia Obat Herbal Bagi Masyarakat - Rosmini; Sri Anjar Lasmini; Andi Ete; Dwi Rohma Wulandari; Nur Edy; Nur Hayati; Asgar Taeyeb (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The cultivation of rare and or wild medicinal plants is one of the strategies to make it easier when needed and also to produce quality simplicia. The partner village program aims to assist the community in carrying out medicinal plant cultivation. The community service activities were carried out in the conservation area of ​​medicinal plants and in the residents' yards in Pakuli Village and lasted for 4 months, from March 2020 to July 2020. The method applied was counseling and technical guidance. The results of the activities showed that the training and technology demonstration were well implemented and were accepted by the community. Counseling activities increase knowledge that is characterized by increased skills when practicing medicinal plants. Species that are cultivated in conservation areas are those that grow wild and rare, while in people's yards it is the species most widely used as medicine and which is of economic value.